Accolade TMZF trunnion corrosion and mechanical failure 9 yr after primary surgery: A case report and treatment options - Matias Hemmilä; Mikko Karvonen; Hannes Keemu; Matti Seppänen; Keijo Mäkelä (Lippincott Williams and Wilkins, 2022)
Preserving patient anatomy in total hip arthroplasty (THA) is important to achieve good functionality and satisfied patients. Modular femoral heads are designed to help achieve this aim by managing limb-length, offset, and soft-tissue balance. Normal anatomy can be more easily preserved, and acetabular component exposure is achieved with removal of the femoral head in revision surgery. However, modularity increases the risk for mechanically assisted crevice corrosion (MACC) (also called trunnion corrosion) and may lead to trunnionosis, adverse local tissue reaction (ALTR), early femoral head dissociation, and implant failure. MACC is a multifactorial and poorly understood phenomenon. Affecting factors can be divided into patient-related, component-related, and surgery-related factors. Patient-related factors include male gender and high body mass index (BMI). Component-related factors include stem design, high-offset implants, head-neck angle, femoral head diameter, and the metal alloy. Surgical-related factors include damage to the head-neck surfaces and inappropriate surgical technique. It has been estimated that 3% of all hip revision procedures worldwide are currently performed due to trunnion corrosion. Femoral head dissociation with implant failure still remains a rare complication, and there are only a few reports of that complication that have been published.
The patient was informed that data concerning the case would be submitted for publication, and he provided consent.